Is Impact Factor True Evaluation for Ranking Quality Measure? - Muneebulla Khan, Khaisar; Hegde, Pradeep (DESIDOC Journal of Library & Information Technology, 2010)
The paper gives the background, meaning and the criteria of the impact factor explaining their terminologies and calculations with examples. It discusses its advantages and the associated problems, and states on the possible misuse and manipulation of the impact factor. The paper concludes with a caution not to finally rely on the impact factor as the only valid measure to rank journal quality and productivity. http://dx.doi.org/10.14429/djlit.29.253